Getting pregnant in HIV clinical trials: women's choice and safety needs. The experience from the ANRS12169-2LADY and ANRS12286-MOBIDIP trials. Issue 6 (1st November 2016) - Serris, Alexandra; Zoungrana, Jacques; Diallo, Mamadou; Toby, Roselyne; Mpoudi Ngolle, Mireille; Le Gac, Sylvie; Coutherut, Julie; Cournil, Amandine; De Beaudrap, Pierre; Koulla-Shiro, Sinata; Delaporte, Eric; Ciaffi, Laura
Abstract : Introduction: Pregnancy is an exclusion criteria in most clinical trials involving antiretroviral therapy (ART) and modern contraception methods are systematically proposed to women of childbearing age. Nevertheless pregnancies are often observed. Reproductive choices during clinical trials should be understood to adapt interventions to the level of risk for mother and baby safety. Our goal was to describe the reproductive behavior and pregnancy outcomes among HIV-infected women on second-line antiretroviral treatment enrolled in two clinical trials and to compare them with those of HIV-positive women in non-research settings. Methods: The number and outcomes of pregnancies were recorded among 281 non menopausal women enrolled in the ANRS 12169-2LADY and ANRS 12286-MOBIDIP clinical trials in Cameroon, Senegal and Burkina Faso. All participants had agreed to use a least one contraceptive method (barrier or non-barrier) which was provided for free during the study. Data were collected through revision of pregnancy notification forms and by data extraction from the study database, regularly updated and checked during the study. Results: Sixty-six women had 84 pregnancies between January 2010 and July 2015 resulting in a pregnancy rate of 8.0 per 100 women-years (WY) (95% CI 6.5–9.9) which is similar to the ones observed in cohort studies in Sub-Saharan Africa (varying from 2.5 to 9.4 pregnancies per 100 WY). Among 60 live births, 10 (16.6%) were born prematurely and 9 (15%) had a low birth weight. Sixteen miscarriages/stillbirths occurred (19.5%). This percentage is comparable to the one expected in the seronegative population which is reassuring for HIV-positive women considering pregnancy on ART. Only one minor birth defect was diagnosed. In univariate and multivariate analysis, miscarriages/stillbirths were not associated either with age, nadir of CD4 count, duration of ART, CD4 count, or viral load at the beginning of pregnancy. Conclusion: HIV-positive women participating in clinical trials conducted in Sub-Saharan Africa tend to get pregnant as often as seropositive women who received medical care in non-research settings. It is therefore essential to adopt a pragmatic approach by re-evaluating the relevance of the criteria for exclusion of pregnant women according to the risk associated with exposure and to seek more effective and innovating contraceptive strategies when using potentially teratogenic molecules.